EVALUATION OF HUMAN LEUKOCYTE ANTIGEN CLASS I AND II ANTIGENS IN HELICOBACTER PYLORI-POSITIVE PEDIATRIC PATIENTS WITH ACTIVE GASTRITIS AND DUODENAL ULCER - Sevim GÖNEN; Sinan SARI; Yaşar KANDUR; Buket DALGIÇ; Oğuz SÖYLEMEZOĞLU (Arquivos de Gastroenterologia, 2017)
ABSTRACT BACKGROUND: As being the first bacteria determined to be carcinogenic, Helicobacter pylori (H. pylori) is a pathogen localized in the stomach in more than half of the world population. Some earlier studies have found a relation between tissue histocompatibility antigens and gastric cancers depending on the regions. OBJECTIVE: The present study aimed to determine the distribution of human leukocyte antigen (HLA) class I and class II antigens in H. pylori-positive pediatric patients with active gastritis and duodenal ulcer, excluding cancer cases, in our center. METHODS: The study included 40 patients diagnosed with H. pylori-positive active gastritis and duodenal ulcer and 100 controls consisting of healthy donor candidates. The HLA class I and class II antigens were studied in the isolated DNA samples using the polymerase chain reaction sequence-specific oligonucleotide probes. RESULTS: The frequency of HLA-B*51 antigen was significantly higher in the patient group than in the control group (40% vs 17%; P=0.003). There was no difference between the two groups in terms of the frequencies of HLA-A, HLA-C, HLA-DR, and HLA-DQ antigens. CONCLUSION: It was determined that HLA-B*51 plays a critical role in H. pylori infection.